Calorie seeking, but not hedonic response, contributes to hyperphagia in a mouse model for Prader–Willi syndrome. (25th June 2015) - Davies, Jennifer R.; Humby, Trevor; Dwyer, Dominic M.; Garfield, Alastair S.; Furby, Hannah; Wilkinson, Lawrence S.; Wells, Timothy; Isles, Anthony R.
Abstract Prader–Willi syndrome (PWS) is a neurodevelopmental disorder caused by deletion or inactivation of paternally expressed imprinted genes on human chromosome 15q11‐q13, the most recognised feature of which is hyperphagia. This is thought to arise as a consequence of abnormalities in both the physiological drive for food and the rewarding properties of food. Although a number of mouse models for PWS exist, the underlying variables dictating maladaptive feeding remain unknown. Here, feeding behaviour in a mouse model in which the imprinting centre (IC) of the syntenic PWS interval has been deleted (PWSICdel mice) is characterised. It is demonstrated that PWSICdel mice show hyperghrelinaemia and increased consumption of food both following overnight fasting and when made more palatable with sucrose. However, hyperphagia in PWSICdel mice was not accompanied by any changes in reactivity to the hedonic properties of palatable food (sucrose or saccharin), as measured by lick‐cluster size. Nevertheless, overall consumption by PWSICdel mice for non‐caloric saccharin in the licking test was significantly reduced. Combined with converging findings from a continuous reinforcement schedule, these data indicate that PWSICdel mice show a marked heightened sensitivity to the calorific value of food. Overall, these data indicate that any impact of the rewarding properties of food on the hyperphagia seen in PWSICdel mice is driven primarily by calorie content and is unlikely to involve hedonic processes. This has important implications for understanding the neural systems underlying the feeding phenotype of PWS and the contribution of imprinted genes to abnormal feeding behaviour more generally.